Cardiac Output Values and Correlation of Renal Injury with Neutrophil Gelatinase-Associated Lipocalin Levels in Off-Pump Coronary Artery Bypass Patients - Şahinalp,Şahin (2020)
Abstract Objective: To investigate the correlation between cardiac output values and renal neutrophil gelatinase-associated lipocalin (NGAL) levels as a biomarker of renal ischemia. Methods: Forty patients, who underwent off-pump coronary artery bypass (OPCAB) surgery and in whom the positioning of the heart was fixed with simple suspension sutures without a mechanical stabilizer, were included in the study. Continuous cardiac output (CO) measurements were recorded using the arterial pressure waveform analysis method (FloTrac sensor system) in the perioperative period. CO was recorded every minute during non-anatomical cardiac positioning for left anterior descending artery (LAD), diagonal artery (D), circumflex artery (Cx), and right coronary artery (RCA) bypasses. Serum NGAL samples were analyzed in the preoperative, perioperative, and postoperative periods. Results: The CO values measured at various non-anatomical cardiac positions during distal anastomosis for LAD, D, Cx, and RCA were significantly lower than pre- and postoperative values measured with the heart in normal anatomical position (3.45±0.78, 2.9±0.71, 3.11±0.56, 3.19±0.81, 5.03±1.4, and 4.85±0.78, respectively, P=0.008). There was no significant difference between CO values measured at various non-anatomical cardiac positions during distal anastomosis. Although there was no significant correlation between NGAL levels and age, duration of surgery, preoperative CO, D-CO, RCA-CO, and postoperative CO measurements, there was a significant correlation between NGAL levels and LAD-CO (P=0.044) and Cx-CO (P=0.018) at the postoperative 12th hour. Conclusion: Full revascularization may be achieved by employing the OPCAB technique while using simple suspension sutures without a mechanical stabilizer and by providing safe CO levels and low risk of renal ischemia.